Analysis of informal housing areas in the city of Hilla using geographic information systems (Journal of the College of Education for Women, 2024)
Random housing is considered one of the most important problems that the city of Hilla suffers from, as this phenomenon has spread throughout all areas of the city with the rapid spread of its urban growth, through encroachment on vacant lands within the city allocated for various land uses, as well as encroachment on agricultural lands and changing their use from productive agricultural places to areas Unplanned residential areas. The spread of slum areas is distributed in the five sectors of the city (Al-Salam sector with 9,378 housing units and a population of 58,461 people, Al-Fayhaa sector with 3,900 housing units and a population of 17,724 people, Al-Fardous sector with 2,607 housing units and a population of 12,770 people, Al-Zuhur sector with 1,380 housing units and a population of 11,782 people, and the Euphrates sector with 900 units Residential The population was 6,553 people, and the number of housing units was (18,165) with a population of (107,290) people, occupying an area estimated at (837.9) hectares until the year 2023. The research dealt with the concept of random housing, which represents neighborhoods that were built in the absence or weakness of law enforcement and legislation. With standards below the required level, many of which were established on municipal lands and agricultural lands, and the classification of slum areas into areas inside the city and areas outside the city. The research also touched on the causes of slum housing, most notably the population increase in the city, the phenomenon of migration from the countryside to the city, family division, and the lack of distribution of plots.